Mushroom consumption and purchasing behaviour in India: A study among selected respondents - Shirur, Mahantesh; Ahlawat, O P; Manikandan, K (Mushroom Research, 2015)
Edible mushrooms are going to be vegetables of future because of their nutritional and medicinal properties and their ability to produce high protein per unit area. However, mushroom as a vegetable is yet to find regular place among commoners. Meagre studies on perception of people on mushrooms and their consumption and purchasing behaviour are coming in the way to have thorough understanding about their prospects as an economic activity and demand in the market. The present investigation conducted over two years among 285 respondents who were trainees attending training on mushroom cultivation technology at Directorate of Mushroom Research, Solan (HP), India. Trainees’ profile, their mushroom consumption behaviour, purchasing behaviour and non purchasing behaviour were studied and descriptive statistics was applied to analyse the data/information. The majority of respondents were male, educated, middle aged and belonged to medium to high income group. The mushroom consumption was found to be relatively less as perceived by themselves. White button mushroom was the most preferred variety followed by oyster mushroom and others. Colour, size and shape of mushroom were precedent over price in deciding their purchasing frequency. Nutritional qualities as well as adding variety to routine diet were equally important for their home consumption. The non purchasing behaviour of respondents highlights the non availability of fresh mushrooms in local market on regular basis. The study also reveals the opinion of people about mushrooms, which helps to arrive at suitable conclusions.